Mobile Pooling and Tracking Order Application for Finance Company - Hanny Fauzia; Tjong Wansen (IT for Society, 2020)
One of the spearheads of finance companies is marketing. Marketing is usually involved directly with customers or suppliers. Things that are usually done by marketing finance companies that enter data order or customer into the system. This system is usually only accessible through computers and corporate networks. The paper proposed the development of such a system on mobile platform so that it can be easily accessed by the users. This application will be very helpful for the marketing of finance companies in providing services to suppliers or customers. Because with this application, marketing can see the order that has been entered and already the extent of the process through their smartphones.